2020
DOI: 10.1088/1361-6587/ab6d47
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing effect of enhanced resistivity on peeling-ballooning instabilities on EAST

Abstract: Previous stability analysis of NSTX equilibrium with lithium-conditioning demonstrates that the enhanced resistivity due to the increased effective charge number Z eff (i.e. increased impurity level) can provide a stabilizing effect on low-n edge localized modes (Banerjee et al 2017 Nucl. Fusion 24 054501). This paper extends the resistivity stabilizing effect to the intermediate-n peeling-ballooning (PB)instabilities with the linear stability analysis of EAST high-confinement mode equilibria in NIMROD two-flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For the mechanism of ELM mitigation, the impurity effects including dilution effect, increased effective charge number Z eff and lower separatrix temperature are usually considered, which can provide a stabilizing effect on the pedestal instabilities [21]. Some simulations have indicated that the enhanced resistivity could also have a stabilizing effect on the peeling-ballooning modes (PBMs) [22,23]. Besides, impurity could also influence the ELM behavior through affecting the pedestal turbulence and thus changing the pedestal gradient and bootstrap current [24].…”
Section: Introductionmentioning
confidence: 99%
“…For the mechanism of ELM mitigation, the impurity effects including dilution effect, increased effective charge number Z eff and lower separatrix temperature are usually considered, which can provide a stabilizing effect on the pedestal instabilities [21]. Some simulations have indicated that the enhanced resistivity could also have a stabilizing effect on the peeling-ballooning modes (PBMs) [22,23]. Besides, impurity could also influence the ELM behavior through affecting the pedestal turbulence and thus changing the pedestal gradient and bootstrap current [24].…”
Section: Introductionmentioning
confidence: 99%
“…Higher Z eff reduces the ion density through dilution effect and edge bootstrap current at higher collisionality, facilitating the stabilization of peeling-ballooning modes (PBMs) [19,22]. Some simulations have also suggested that the enhanced resistivity due to increased Z eff could also provide a stabilizing effect on the PBMs [23,24].…”
Section: Introductionmentioning
confidence: 99%